Evidence for a monoclinic MA to tetragonal morphotropic phase transition in (1-x)[Pb(Fe1/2Nb1/2)O3]- xPbTiO3 ceramics - Singh S.P.; Singh A.K.; Pandey D. (My University, 2025)
The results of a powder x-ray diffraction study of the evolution of the crystal structure in pyrochlore-free single-phase powders of (1-x)[Pb(Fe 1/2Nb1/2)]O3-xPbTiO3 (PFN-xPT) are presented. Rietveld analysis of the powder diffraction data reveals that the morphotropic phase transition in PFN-xPT corresponds to a change of structure from MA-type monoclinic with Cm space group to tetragonal with P4mm space group at 0.06<x<0.08. It is argued that this monoclinic phase persists in the entire composition range 0.0≤x≤0.06, as evidenced by the presence of anomalous broadening of the 200 profile. The similarity of the morphotropic phase boundary (MPB) in PFN-xPT with that in the Pb(Zr xTi1-x)O3 (PZT) is pointed out. © IOP Publishing Ltd.